2020
DOI: 10.26434/chemrxiv.12336635.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure-Based Virtual Screening and Molecular Dynamics of Phytochemicals Derived from Saudi Medicinal Plants to Identify Potential COVID-19 Therapeutics

Abstract: Coronavirus disease 2019 (COVID-19) has affected almost every country in the world by causing a global pandemic with a high mortality rate. Lack of an effective vaccine and/or antiviral drugs against SARS-CoV-2, the causative agent, has severely hampered the response to this novel coronavirus. Natural products have long been used in traditional medicines to treat various diseases, and purified phytochemicals from medicinal plants provide a valuable scaffold for the discovery of new drug leads. In the present s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Quercetin showed inhibitory activity against SARS-CoV PL pro , although Papyriflavonol A was the most effective inhibitor of PL pro among those studied by Park et al (2017). Virtual structurebased screening revealed that withanolide A, isocodonocarpine, and calonysterone bind to PL pro (Alamri et al, 2020).…”
Section: Structure-activity-relationship Approachmentioning
confidence: 95%
“…Quercetin showed inhibitory activity against SARS-CoV PL pro , although Papyriflavonol A was the most effective inhibitor of PL pro among those studied by Park et al (2017). Virtual structurebased screening revealed that withanolide A, isocodonocarpine, and calonysterone bind to PL pro (Alamri et al, 2020).…”
Section: Structure-activity-relationship Approachmentioning
confidence: 95%
“…These amino acids interact with human ACE 2, too; it means these amino acids are proper residues for binding to any compound and inhibition of SPIKE of virus following that. This compound has properly binding energy for SPIKE of the virus compared to the same molecules, including some FDA-approved drugs or same designed and modified molecules, which was mentioned earlier; also there is a report of mulberrofuran G appropriate affinity to binding to 3cl-protease of SARS corona virus 2 (11); according to these reports, mulberrofuran G can be a potent candidate for the treatment of COVID-19. However, it needs more tests, such as in vitro and in vivo and clinical trials, to confirm its efficacy.…”
Section: Discussionmentioning
confidence: 80%